2020
DOI: 10.1038/s12276-020-0431-z
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblast-secreted exosomal miR-423-5p promotes chemotherapy resistance in prostate cancer by targeting GREM2 through the TGF-β signaling pathway

Abstract: Therapeutic failure in prostate cancer (PC) is believed to result from its unusually invasive and metastatic nature. Cancer-associated fibroblasts (CAFs) are essential in the tumor microenvironment. We intended to study the role of CAF-derived exosomes in the context of PC and the potential regulatory mechanism associated with miR-423-5p and GREM2. CAF-derived exosomes decreased the chemosensitivity of parental PC cells and enhanced the drug resistance of drug-resistant cells. PC-associated fibroblast-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 45 publications
(50 reference statements)
1
57
0
Order By: Relevance
“…This induced resistance was due to miR-27a derived exosomes that regulated the expression of Trp53 [99]. A third study showed that CAF-secreted exosomal miR-423-5p promoted resistance to docetaxel or bicalutamide in PCa cells LNCaP, 22RV1 and C4-2 cells, respectively, by targeting GREM2 [100].…”
Section: Role Of the Microenvironmentmentioning
confidence: 95%
“…This induced resistance was due to miR-27a derived exosomes that regulated the expression of Trp53 [99]. A third study showed that CAF-secreted exosomal miR-423-5p promoted resistance to docetaxel or bicalutamide in PCa cells LNCaP, 22RV1 and C4-2 cells, respectively, by targeting GREM2 [100].…”
Section: Role Of the Microenvironmentmentioning
confidence: 95%
“…Similar to what was observed in cases of chemo-resistance against DNA damaging agents, miRNAs are involved in the activation of TGF-β signaling in cells treated with anti-metabolites and anti-microtubule drugs. Examples of miRNA regulators of TGF-β signaling include miR-423-5p, miR-552, and miR-17–92 cluster (miR-17, miR-18a, miR-19a, miR-19b, miR-20a and miR-92a) in prostate cancer, colorectal cancer, and pancreatic cancer ( Cioffi et al, 2015 ; Zhao et al, 2019 ; Shan et al, 2020 ). Intriguingly, TGF-β/SMAD signaling activation directly induced G1 cell-cycle arrest in SCC cells, leading to the entry of tumor-propagating cancer cells (TPCs) into quiescence, which protected cancer cells from DNA damage caused by 5-FU treatment by adopting a condensed heterochromatic state ( Brown et al, 2017 ).…”
Section: Tgf-β Signaling and Resistance To Chemotherapymentioning
confidence: 99%
“…Additionally, exosomal miR-92a-3p derived from colorectal CAF targets anti-tumor F-box/WD repeat-containing protein 7 (FBXW7) and a modulator of apoptosis 1 (MOAP1), thereby endowing chemoresistance to cancer cells ( Hu et al, 2019 ). In line, exosomal miRNA was demonstrated to confer chemoresistance in prostate cancer ( Shan et al, 2020 ) and head and neck cancer ( Qin et al, 2019 ). CAF-derived exosomal long non-coding RNA (lncRNA) H19 was exhibited to enable stemness expression by sponging miR-141 that targets β-catenin ( Ren et al, 2018 ).…”
Section: Cancer-associated Fibroblast As a Dynamic Player In Promoting Cancer Stemnessmentioning
confidence: 99%